Plasmapheresis with corticosteroids and antiviral: a life-saving treatment for severe cases of Covid 19 (A case report) - Mohammad Bagherzadeh; Mahmoud Parham; Somayeh Zohali; Sedighe Molaii; Jamshid Vafaeimanesh (Babol University of Medical Sciences, 2020)
Background: COVID-19 pandemic is a global concern. In this study we suggest using a novel three-dimensional treatment mainly based upon immune system modulation to revolve the virus chaos, regarding to the cytokine storm introduced as the main character of COVID-19 infection scenario. Case Presentation: A young man infected by 2019-nCoVwho suffered from respiratory arrest and loss of consciousness(On March 27,2020), undergoes cardiopulmonary resuscitation and then Endotracheal  intubation and upon ICU administration and confirmed diagnosis of COVID-19, Considering critical condition of the young patient, plasmapheresis was performed once on a daily basis, three doses of interferonbeta(IFN-β-1b) was injected subcutaneously every other day and dexamethasone was given at a dose of 4 mg every 8 hours (TID).After 2 days, the patient was extubated and transferred from the ICU to the ward (March 31,2020) where plasmapheresis was performed 4 times daily for 4 days.Finally ,after 7 days of hospitalization, the patient was discharged with a good general condition. Conclusion: we modulated immune system through plasmapheresis to sweep out the released cytokines and corticosteroid along with interferon andcommon antiviral treatments. Our data suggest this combined method to be effective for critically ill COVID-19 patients.